2020
DOI: 10.1093/fampra/cmaa068
|View full text |Cite
|
Sign up to set email alerts
|

Far from acceptable: youth-reported risk behaviour screening by primary care physicians

Abstract: Abstract Background Adolescence and early adulthood are periods of experimentation during which health detrimental behaviours might be acquired. Objective This study’s purpose is to evaluate physicians’ likelihood of addressing health risk behaviours with youths d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, in our study, the health issues discussed depended heavily on the school doctor, suggesting that the discussion was not always patient-centred. This is consistent with the findings of a recent Swiss study of young adults (aged 17-26 years), which showed that the likelihood of risk behaviours being addressed by primary care physicians was largely independent of the risk factors and wishes of the youth [26]. Moreover, consistent with previous studies [37], the most frequently addressed health topics were "exercise, nutrition and health protection" and "stimulants and addictive substances".…”
Section: Original Articlesupporting
confidence: 91%
See 1 more Smart Citation
“…However, in our study, the health issues discussed depended heavily on the school doctor, suggesting that the discussion was not always patient-centred. This is consistent with the findings of a recent Swiss study of young adults (aged 17-26 years), which showed that the likelihood of risk behaviours being addressed by primary care physicians was largely independent of the risk factors and wishes of the youth [26]. Moreover, consistent with previous studies [37], the most frequently addressed health topics were "exercise, nutrition and health protection" and "stimulants and addictive substances".…”
Section: Original Articlesupporting
confidence: 91%
“…Our inferential results are also well in line with the literature: the association of both lower socioeconomic status [24][25][26] and female gender [6,24,27,28] with unfavourable self-reported health status is well documented. For instance, the HBSC survey found that adolescents from less wealthy families and female adolescents reported lower levels of life satisfaction and health [18,24].…”
Section: Original Articlesupporting
confidence: 91%
“…Many primary care practices rely on paper adolescent screening tools. However, these tools are often not completed by patients and results of the paper screening are inconsistently recorded in the electronic health record (EHR), making it difficult to monitor individual or population-level risk behaviors over time [ 7 ]. Electronic data capture for adolescent risk behavior screening has several potential advantages over paper screening and is generally preferred by adolescents [ 8-10 ], including those engaging in high-risk behaviors [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, based both in Switzerland and in the United States, 10 , 11 have shown that although adolescents regularly consult their primary care provider (PCP), they are not routinely screened for psychosocial risk behaviours such as alcohol or drug consumption, eating issues, or suicidal behaviours. 12 , 13 Barriers to behavioural risk screening have previously been established to be insufficient financial compensation, insufficient consulting time, or lack of resources and this is independent of the health system examined. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%